Penghentian Penyidikan Tindak Pidana Pembunuhan Dalam Kaitan Dengan Pembelaan Terpaksa - Azis, Abdul; Hehanussa, Deassy Jacomina Anthoneta; Supusepa, Remon (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
Forced defense (noodweer) is an act of defending oneself in a situation of pressure for an attack. In other words, in an act of self-defense, someone has received an unexpected or unknown attack. Any person who commits an act of forced defense for himself or another person, his own or another person's honor, morals or property, because there is an attack or threat at that time which is against the law, against himself or another person, against his own honor or morals or property. nor anyone else. The aim of this research is to examine and analyze the basis for terminating investigations into criminal acts of murder in relation to forced defense. And the termination of the investigation into the crime of murder in connection with the forced defense was in accordance with applicable procedures. This type of research is normative juridical in nature. The research type is descriptive-analytical. Sources of legal materials use primary legal materials and secondary legal materials. Techniques for collecting legal materials through literature study and qualitative analysis of legal materials. The results of the research show that the basis for terminating an investigation into a criminal act of murder in connection with forced defense is Article 49 paragraph (1) of the Criminal Code (KUHP), whoever commits an act of forced defense for himself or for another person, honor, morality or property. own or other people's property, because there is an attack or threat at that time which is against the law, against oneself or another person, against the honor of morality or one's own or another person's property. However, not all law enforcement officers have the authority to provide assessments in relation to Forced Defense (Noodweer), the law enforcement officers who have the authority to decide whether a criminal act of murder can be stopped in relation to forced defense are the Prosecutor at the prosecution stage and the Judge at the trial stage. And the termination of the investigation into criminal acts of murder in connection with the defense is forced to include cases that are in accordance with procedures, and there are also cases that are not in accordance with procedures.